FC096: Von Willebrand Factor: A Central Regulator of Arteriovenous Fistula Maturation. (3rd May 2022) - Laboyrie, Suzanne; De Vries, Margreet; Martinez, Laisel; Vazquez-Padron, Roberto; Rotmans, Joris
Abstract: BACKGROUND AND AIMS: Nonmaturation of arteriovenous fistulas (AVFs) remains a bottleneck in creating a long-lasting lifeline to hemodialysis. AVF maturation is determined by the intricate balance between outward remodeling (OR) and formation of intimal hyperplasia (IH), both processes in which vascular smooth muscle cell (VSMC) proliferation is crucial. Recently, we observed that von Willebrand Factor (vWF) is an essential protein in AVF maturation in mice, through its induction of VSMC proliferation and thereby positive effect on OR. In this study we investigate the role of vWF in human AVFs. METHOD: Humane plasma and patient-matched samples were obtained during two stage brachio-basalic AVF surgery: native veins were collected at time of AVF creation and venous AVF samples at time of transposition or salvage procedure. Random selection was performed using propensity score matching while adjusting for age, sex, ethnicity, diabetes, and dialysis status. AVF maturation was defined as a luminal AVF diameter of >6 mm using intravascular probes. Sixteen mature AVFs and 15 failed AVFs were available for matched-pair analysis. Histological samples were stained for vWF, CD31 and aSMA. Positively stained tissue in the medial layer was quantified using Histoquant and analyzed with the Wilcoxon signed-rank test. Intima/media (I/M) area ratio was calculated by dividing the IH by the medial layer. vWF antigen levels in patient plasma were determined by ELISA for 8 patients with AVF failure and 10 with AVF maturation. RESULTS: vWF is expressed in the IH, tunica media and vasa vasorum of ESRD (end-stage renal disease) patient AVFs. Furthermore, aSMA + /vWF + co-localization was observed in tunica media of matured AVF. Although no difference in IH was observed across the pair-matched samples of patients with matured versus failed AVFs, the I/M ratio increased from the native vein to the venous AVF sample with 2.6-fold in mature AVFs (P = 0.02) and 4.0-fold in failed AVFs (P = 0.0001). Concurrently, OR, wall thickening and luminal area were significantly increased 2.1-fold (P = 0.02), 6.6-fold (P = 0.009) and 4.7-fold (P = 0.02), respectively, in patients with matured AVFs compared to failed AVFs. While there was no difference in systemic vWF antigen levels between groups or before versus after AVF creation, wall thickening and OR coincided with 167% ( P  = 0.03) increase in vWF expression in the medial layer of preaccess veins to matured venous AVF samples, but not in patient samples of failed AVFs (Figure 1 ). Moreover, we observed a reduction of vWF + endothelial cells lining the intima, from the native vein to the venous AVF outflow tract. Matured AVFs presented with 3.6-fold more vWF + intima than failed AVF samples (P = 0.04). The I/M ratio and vWF + intima of AVFs were negatively correlated using linear regression: when the vWF + intimal layer is disrupted, the I/M ratio increases (Figure 2 ; slope P = 0.0017 for matured AVFs and P = 0.0264 for failed AVFs). CONCLUSION: Our results suggest that vWF is involved in AVF maturation in ESRD patients through its local action. Despite comparable systemic vWF antigen levels between between patient groups, matured AVFs show increased local vWF expression in the intimal layer and tunica medica, coinciding with increased venous wall thickening as well as outward remodeling.